Poststroke epilepsy incidence, risk factors and treatment: German claims analysis. (24th February 2021) - Hardtstock, Fränce; Foskett, Nadia; Gille, Patrick; Joeres, Lars; Molzan, Manuela; Wilson, Jessica Claire; Wilke, Thomas; Holtkamp, Martin
Abstract : Objectives: To describe incidence, risk factors, and treatment of poststroke epilepsy (PSE) in Germany based on claims data. Methods: Retrospective analysis of claims data from a German public sickness fund (AOK PLUS). Patients with acute stroke hospitalizations from January 01, 2011 and December 31, 2015 (index hospitalization) were followed for 12–72 months. Outcomes included incidence of PSE (patients with ≥2 seizure claims [during/after index hospitalization], or ≥1 seizure claim after index hospitalization), multivariate Cox‐regression analyses of time to seizure claim and death after index stroke hospitalization discharge, and antiepileptic drug (AED) treatment. Results: Among 53 883 patients with stroke (mean follow‐up of 829.05 days [median 749]), 6054 (11.24%) had ≥1 seizure claim (mean age 73.95 years, 54.18% female). 2130 (35.18%) patients had a seizure claim during index hospitalization (indicative of acute symptomatic seizures). Estimated incidence of PSE (cases/1000 patient‐years) was 94.49 within 1 year. Risk of seizure claim following hospital discharge was higher in patients with hemorrhagic stroke (hazard ratio [HR] =1.13; p <.001) vs those with cerebral infarction. Seizure claim during index hospitalization was a risk factor for seizure claims after hospital discharge (HR =6.97; p <.001) and early death (HR =1.78; p <.001). In the first year of follow‐up, AEDs were prescribed in 73.75% of patients with seizure claims. Conclusions: Incidence of PSE was in line with previous studies. Hemorrhagic stroke and seizure claim during index hospitalization were risk factors for seizure claims after hospital discharge. Most patients with seizure claims received AED treatment.